The radio-protective effects of n-Hexane extracts of Telfairia occidentalis Hook. f. and Cucumeropsis mannii Naud. seed oils on the liver of irradiated male Wistar rats - NWOZO, Sarah Onyenibe; UKEJE, Michael O; IFIE, Josiah Eseoghene (Plant Science Today, 2020)
The human population is predisposed to some considerable amounts of radiation especially ionizing radiation which may negatively impact their metabolic processes. Herbal extracts can mitigate these harmful effects. Therefore, this study aims to investigate the protective effect of n-Hexane extracts of Telfairia occidentalis and Cucumeropsis mannii seeds oils against radiation-mediated oxidative stress in Wistar rats. Sixty male rats were randomly distributed into six groups of six animals each and n-hexane extracts of T. occidentalis and C. mannii were administered at a dose of 2.4 or 4.8 mg/kg b. wt., orally for 7 days before irradiation and 10 days after irradiation, when they were sacrificed. Lipid peroxidation was measured, hepatic antioxidant status; SOD, CAT, GSH, Gpx and GST were estimated. The activities of liver enzymes: ALT, AST and ALP were measured and histological examination of sections of the liver was carried out. Radiation significantly increased MDA levels, SOD, GPx, AST, ALT and ALP activities but reduced body weights, total proteins, CAT, GSH and GST activities. Administration of the extracts significantly reduces the levels of MDA, SOD, GPx, ALT, AST and ALP activities while they increase the activities of CAT, GSH and GST at a dosage of 4.8 mg/kg. Histological examination showed increased levels of toxicity in radiated and groups administered 2.4 mg/kg extracts. From these findings, extracts of T. occidentalis and C. mannii at 4.8 mg/kg b. wt are effective herbal remedies in the prevention and amelioration of the consequences of oxidative stress due to exposure to ionizing radiation.